Information system analysis: design consideration of active database / Sharina Mohd Nasir - Mohd Nasir, Sharina (2005)
In the rapidly changing environment of the knowledge economy, an enterprise must respond to potential fiiture changes when developing and implementing enterprise systems, which must be thus flexible and integrateable. The concepts of virtual enterprise, supply chain and B2B e-business have been widely employed in business development. Since the essence of these concepts is "enterprise integration", the importance of information sharing among enterprises is increasing. This research is meant to look at the core of this integration and sharing environment; the active databases system design by which active database is a database technology for supporting application in heterogeneous information system. This research presents the result of an empirical study of design consideration of data model for the active databases in the enterprise environment. The objectives of this study are to identify the roles and functionalities of active databases, the most common data model being used for active databases and the recommendation of the optimized data model for active databases. The researcher has conducted interview sessions with 7 selected companies from various business areas to get the primary data by using a set of questionnaires as the research instrument. The results indicate that the most common type of data model being used by the involved companies is relational data model and followed closely by object-oriented data model. The results also reveal that the roles and functionalities of active databases being implemented includes to supply data at real-time, to detect event, to execute rules, and for provisioning. The recommended optimized data model for active databases is object oriented data model by which it generates more advantages differed to the relational data model. This research also provides several recommendations at the final section of the report that should be considered upon this research.